Basic features of Islamic culture - "Ali, Abbas" (New Delhi, 2006)
Islam is essentially monotheistic faith, and the Muslims believe in the existence of one, the cherisher and the maintainer of the world who is without a second. Broadly speaking Islam is based on two principles, two fundamental (3z(B(1) Belief in God and (2) consciousness of moral obligations towards others. The Muslim Shariah which means the law concerning the organisation of relations between individuals, as members of Societies and as citizens of States, is, in reality, a moral code based on the fundamental principles of a belief in almighty and in the treatment of his creatures, as class deserving justice and sympathy.s
Keywords: Islamic culture